AKURASI PERKIRAAN POPULASI ANJING LIAR SEBAGAI RISIKO HEWAN PENULAR RABIES DI EMPAT KECAMATAN KOTA BANDA ACEH MENGGUNAKAN SOFTWARE APSP (The Estimation Accuracy of Stray Dogs Population as a Risk of Rabies Transmission in Four Sub-District of Banda Aceh Using APSP Software) - Syehaffer Wahyudi Affandi; Teuku Reza Ferasyi; Nurliana Nurliana; Zakiah Heryawati Manaf; Sulasmi Sulasmi; Razali Razali (Universitas Syiah Kuala, 2015)
This study aimed to test the estimation accuracy of stray dogs population using video camera equipped with software of animal perception of seismic phenomena (APSP) and manually observation which counting the number of biting cases by rabies-risk animals (RRA) in four sub-districts of Banda Aceh (grouped as highest and lowest reported biting cases). This study was conducted by direct observation and counting the number of stray dogs around rubbish bin at night (10.00-12.00 pm) in each sub-district, the counting was repeated 3 times at the same time on different day. The data was analyzed using world society for the protection of animals (WSPA) methods. Overall, the results showed that the number of stray dogs around rubbish bin in four sub-districts were highest based on manual counting method as compared to counting by using video camera equipped with APSP software. The numbers of stray dogs were high in the sub-districts with higher reported bitting cases by RRA. As conclusion, counting of stray dogs by using manual methods is still more reliable than using video camera equipped with APSP software.Key words: rabies, stray dogs, population, software APSP